Pecking Order Theory and Financing Decisions: Evidence from African Small and Medium-Sized Enterprises - Kounouwewa, Jules; Azon, Aimé Togodo (International Journal of Economics and Financial Issues, 2025)
Small and medium-sized enterprises (SMEs) are widely recognized as the backbone of African economies, yet they face persistent financing constraints that limit growth and competitiveness. Understanding how these firms prioritize financing sources is therefore central to both academic debates and policy interventions. This paper investigates the relevance of the Pecking Order Theory (POT) in explaining financing decisions of African SMEs, focusing on whether firms follow the hierarchical order of using internal funds first, then debt, and finally external equity when facing financing needs. Drawing on firm-level data from recent World Bank Enterprise Surveys and complementary national datasets, we test the applicability of POT using the financing-deficit approach proposed by Shyam-Sunder and Myers (1999) and dynamic panel models to account for heterogeneity across countries, firm age, and sector. The results show partial support for POT. Consistent with theory, African SMEs demonstrate a strong preference for internal financing, followed by debt when internal resources are insufficient. However, deviations emerge in contexts of high credit constraints, weak collateral systems, and underdeveloped financial reporting practices, where some firms rely directly on external equity, grants, or owner injections. Regulatory quality and country-level institutional environments further moderate the hierarchy of financing, with firms in more transparent and stable settings adhering more closely to POT predictions. This study contributes to the literature by providing cross-country African evidence on SME capital structure, highlighting how institutional frictions and firm-specific factors shape financing behavior. The findings have practical implications: for managers, sequencing financing in line with POT can reduce costs of capital and dependence on external equity; for policymakers, strengthening credit information systems, collateral registries, and SME accounting frameworks could improve debt access and reinforce efficient financing hierarchies. Overall, the paper underlines that while POT remains a useful benchmark, African SMEs’ financing decisions are shaped by both firm-level opacity and broader institutional constraints. These insights expand the theoretical and practical understanding of capital structure in emerging economies and inform policies aimed at bridging the SME financing gap.